Noise Levels Associated with Sentiment Analysis on Twitter: A Case Study of New York City - Yu, Xiang. (2017)
Abstract: Resulting from the urbanization and motorization, urban noise has become one of the most severe hazards in current society. This thesis firstly investigated the background of noise-control regulations and laws, how noise varies in different urban environment, and the health impacts of noise pollution. After that, the author made several maps to illustrate the information such as distribution of 311 noise complaints and population density in New York City via ArcGIS. Finally, this thesis explored how to use social media data (Tweets) to determine the correlations among different types of variables including population density, average noise complaints, and average sentiment scores in New York City, and two methods, sentiment analysis and statistical test were applied in this process. The results of this study demonstrated that noise complaint and population density were significantly correlated and moved together positively. Meanwhile, the relationship between noise complaint and sentiment score were beyond the author's expectation. It had been approved in this study that when noise complaints go up the sentiment of tweets becomes more negative than positive in most of the community boards in New York City. In addition, this thesis also provided some suggestions and recommendations on applying social media data in urban planning and strategies of noise control for policy makers and future studies.; Thesis (M.A.)--Tufts University, 2016.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Justin Hollander.; Committee: Mary Davis.; Keyword: Urban planning.